2006
DOI: 10.1038/sj.npp.1301016
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Betamethasone Decreases Anxiety in Developing Rats: Hippocampal Neuropeptide Y as a Target Molecule

Abstract: Repeated antenatal administration of betamethasone is frequently used as a life-saving treatment in obstetrics. However, limited information is available about the outcome of this therapy in children. The initial prospective studies indicate that there are behavioral impairments in children exposed to repeated courses of prenatal betamethasone during the third trimester of pregnancy. In this study, pregnant rats received two betamethasone injections on day 15 of gestation. Using immunohistochemistry, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 77 publications
6
26
1
Order By: Relevance
“…In experimental animals, prenatal treatments with betamethasone or dexamethasone have anticonvulsant effects in the kindling model (Velíšek 2005, Young, et al 2006). In developing offspring, prenatal betamethasone increases hippocampal expression of anticonvulsant neuropeptide Y (NPY) (Heilig, et al 1993, Velíšek 2006b), corroborating thus findings of anticonvulsant effects of prenatal betamethasone or dexamethasone exposure in kindling epileptogenesis.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In experimental animals, prenatal treatments with betamethasone or dexamethasone have anticonvulsant effects in the kindling model (Velíšek 2005, Young, et al 2006). In developing offspring, prenatal betamethasone increases hippocampal expression of anticonvulsant neuropeptide Y (NPY) (Heilig, et al 1993, Velíšek 2006b), corroborating thus findings of anticonvulsant effects of prenatal betamethasone or dexamethasone exposure in kindling epileptogenesis.…”
Section: Introductionsupporting
confidence: 69%
“…each) at 08:00 and 18:00 (all drugs were purchased from Sigma, St. Louis, MO, USA, unless stated otherwise). These doses were found effective in previous studies (Velíšek 2006b) and in pilot experiments. Control pregnant rats received two i.p.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Individual rats were placed at the distal end of one open arm, facing away and released, and the latency to enter last the third of a closed arm was measured. This latency, referred to as transfer latency (TL), was chosen to preferably test anxiety than to include simple exploratory activities [25]. Forced swim tests were performed to assess depressive-like behaviors as previously described [26][27][28], with some modifications.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Treatment protocols do not show a preference for one in particular, since meta-analysis of different studies directly comparing DEX with betamethasone found no statistically significant differences [38, 39]. The impact of DEX, prenatally administrated in rodents, has been studied in more detail since it is associated with central nervous system (CNS) negative effects [7, 40, 41]. …”
Section: Discussionmentioning
confidence: 99%